6x+4(x-3)=13

Simple and best practice solution for 6x+4(x-3)=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+4(x-3)=13 equation:


Simplifying
6x + 4(x + -3) = 13

Reorder the terms:
6x + 4(-3 + x) = 13
6x + (-3 * 4 + x * 4) = 13
6x + (-12 + 4x) = 13

Reorder the terms:
-12 + 6x + 4x = 13

Combine like terms: 6x + 4x = 10x
-12 + 10x = 13

Solving
-12 + 10x = 13

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 10x = 13 + 12

Combine like terms: -12 + 12 = 0
0 + 10x = 13 + 12
10x = 13 + 12

Combine like terms: 13 + 12 = 25
10x = 25

Divide each side by '10'.
x = 2.5

Simplifying
x = 2.5

See similar equations:

| 92x=883.2 | | 2X-6=3X+7 | | x=150+0.85(x) | | w-147.67=144.67 | | 3/5x21=3x | | .3333p+7=12-.6666p | | (2x^2)/(0.8-x^2)=53.3 | | 3/5+3=21x | | z/325=7 | | z/23=6 | | 1/9p=5/6 | | x=200+0.8(x) | | -5(X-4)+8X=6X-2 | | -6y-9=-3(y+9) | | x+65=50+75 | | 10/27=5/9t | | z^23=6 | | 18y-6=8y-70 | | 50+75=x+65 | | 5(X+4)/6=2X-5 | | 0.2x+1-2=0.5 | | x+(.01x)=15000 | | D=7/3(m-76) | | 2x/2-3x-1=0 | | 5x-3/2+6=-11 | | x-(0.01*x)=1500 | | -7-35/8 | | -6+x-8=24 | | x-(0.1*x)=1500 | | x^2-6x+12=8 | | 8(X-8)=7(X-8) | | 25=-5+x-7 |

Equations solver categories